Improvement of the anticollision method "Velocity Obstacle" by taking into consideration the dynamics of an operating vessel - Aleksishin, Andriy; Vagushchenko, Aleksandr; Vagushchenko, Oleksandr; Kalinichenko, Yevgeniy (Eastern-European Journal of Enterprise Technologies, 2019)
This paper has proposed an algorithm that accounts for the dynamics of an operating vessel within the Velocity Obstacle collision prevention method. This algorithm provides the basis for selecting joint maneuvers by course and speed with the assigned start for divergence with multiple "targets" by determining, applying a sorting method, a representative set of acceptable maneuver options. In order to employ the method of sorting, we have selected the ranges of change in the maneuver parameters (course and speed) and performed their sampling at a small enough step. One finds, for all pairs of discrete values of change in the course and speed, taking into consideration the dynamics of an operating vessel, a trajectory and duration of a maneuver, with determining, at the time it ends, the location of an operating vessel and "targets", as well as it is to be established if it is accompanied by the intersection of "target" danger domains. If none of these domains is crossed, the maneuver option is considered acceptable. The totality of such joint changes in course and speed, derived from sorting, creates a set of permissible maneuver options. When finding this set, the dynamics of an operating vessel is taken into consideration simplistically. It is believed that the turns are performed at a constant angular speed, a change in the linear speed at braking can be represented by a power polynomial of second order, and changes in course and speed in the joint maneuver are independent. The "targets" involve circular danger domains whose center is shifted, from a "target's" center of mass to the stern, by 1/3 of the domain's radius. This radius has been amended to include the size of a "target" and an operating vessel. To test the resulting algorithm, the software has been developed in the Borland Delphi programming language. Employing it for calculations has confirmed the operability of the algorithm. That enables the derivation, in real time, of a set of velocity vectors for divergence taking into consideration the dynamics of own vessel, which makes it possible to improve the accuracy of forecasting and the safety of calculated maneuvers. The use of displaced circular danger domains for "targets" makes it possible to take into account the unequal degree of risk when crossing their course along the bow and stern